Investigating Diglossic Situation in Watunohu Communities, North Kolaka Regency, Southeast Sulawesi - Fitra, Muh. Al Fachrizah; Wati, Nirmawati (Fakultas Sastra - Universitas Muslim Indonesia, 2022)
This study takes a look at goals to decide the language used and to decide the state of affairs of diglossia withinside the community in Watunohu district, North Kolaka regency, Southeast Sulawesi. The technique used in this research is descriptive qualitative, the usage of descriptive methods. The series of records strategies in this research had been remark and interviews. The diglossia records primarily based totally on shape seven domains, namely the realm of the family, the realm of association, the realm of buying and selling transactions, the realm of religion, the realm of government, the realm of education, and the realm of the profession or job. Based on the research findings, it indicates that the human beings in Watunohu district are bilingual. It can be visible from the language used. Research based on the realm of the family, the realm of association, the realm of buying and selling transactions, and the realm of religion display that the community is greater dominant in the usage of the Bugis language while the realm of government, the realm of education and the realm of the profession, display that Indonesian is greater dominantly used as quite a few better languages.